Nutritional Value of Cookies made from the mixture of Mocaf flour (Modified Cassava Flour) and Ketapang seeds (Terminalia catappa L.) - Yenrina, Rina; Anggraini, Tuty; Kadri, Annesa (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
Efforts in developing food products continue to be carried out such as utilizing local commodities so that non-wheat flour processing can be used as a substitute for making food products in order to overcome dependence on wheat flour. One such effort is to make cookies from local ingredients, modified cassava flour known as MOCAF (Modified cassava flour). This research was aimed to determine the effective mixture of Mocaf flour and ketapang seed on the characteristic of cookies based on nutritional value. The research design used a completely randomized design (CRD), with 5 treatments and 3 replications. This data was analyzed with ANOVA (analysis of variance) and if the data was significantly different analyzed continued with Duncan’s New Multiple Range Test (DNMRT) at the level 5%. The treatments used were A (100% Mocaf flour : 0% Ketapang seed), B (90% Mocaf flour : 10% Ketapang seed), C (80% Mocaf flour : 20% Ketapang seed), D (70% Mocaf flour : 30% Ketapang seed), E (60% Mocaf flour : 40% Ketapang seed). The results showed that the Mocaf flour and ketapang seed comparison significantly influenced the protein content, fat content, energy, texture, free fatty acid, and carbohydrate content, but not significantly affect moisture content and ash content.